A Peroxisomal Disorder of Severe Intellectual Disability, Epilepsy, and Cataracts Due to Fatty Acyl-CoA Reductase 1 Deficiency - Buchert, Rebecca; Tawamie, Hasan; Smith, Christopher; Uebe, Steffen; Innes, A. Micheil; Al Hallak, Bassam; Ekici, Arif Bülent; Sticht, Heinrich; Schwarze, Bernd; Lamont, Ryan E.; Parboosingh, Jillian S.; Bernier, Francois P.; et al. (American Journal of Human Genetics, 2014)
Rhizomelic chondrodysplasia punctata (RCDP) is a group of disorders with overlapping clinical features including rhizomelia, chondrodysplasia punctata, coronal clefts, cervical dysplasia, congenital cataracts, profound postnatal growth retardation, severe intellectual disability, and seizures. Mutations in PEX7, GNPAT, and AGPS, all involved in the plasmalogen-biosynthesis pathway, have been described in individuals with RCDP. Here, we report the identification of mutations in another gene in plasmalogen biosynthesis, fatty acyl-CoA reductase 1 (FAR1), in two families affected by severe intellectual disability, early-onset epilepsy, microcephaly, congenital cataracts, growth retardation, and spasticity. Exome analyses revealed a homozygous in-frame indel mutation (c.495_507delinsT [p.Glu165_Pro169delinsAsp]) in two siblings from a consanguineous family and compound-heterozygous mutations (c.[787C>T];[1094A>G], p.[Arg263(*)];[Asp365Gly]) in a third unrelated individual. FAR1 reduces fatty acids to their respective fatty alcohols for the plasmalogen-biosynthesis pathway. To assess the pathogenicity of the identified mutations, we transfected human embryonic kidney 293 cells with plasmids encoding FAR1 with either wild-type or mutated constructs and extracted the lipids from the cells. We screened the lipids with gas chromatography and mass spectrometry and found that all three mutations abolished the reductase activity of FAR1, given that no fatty alcohols could be detected. We also observed reduced plasmalogens in red blood cells in one individual to a range similar to that seen in individuals with RCDP, further supporting abolished FAR1 activity. We thus expand the spectrum of clinical features associated with defects in plasmalogen biosynthesis to include FAR1 deficiency as a cause of syndromic severe intellectual disability with cataracts, epilepsy, and growth retardation but without rhizomelia.
EVALuna2:9238